BREAKING DOWN THE GENDER CONSTRUCTION: FEMINIST CRITICISM IN SINAR MATA IBU BY HARRIS EFFENDI THAHAR - Tesaannisa Tesaannisa (Universitas Pahlawan Tuanku Tambusai, 2023)
The division of roles and distinctions between the traits of men and women are products of the construction of gender in a deeply ingrained society. Because each sex can exhibit masculine or feminine traits depending on the circumstance and condition, these roles and characteristics cannot be used as a binary opposition in practice. The short story